(untitled) (Research, Society and Development, 2022)
Cancer patients are generally submitted to chemotherapy and radiotherapy, which tend to cause problems related to intense inflammatory processes, malnutrition, nausea and emesis. Therefore, performing supplementation in these patients is important and necessary, as it favors cancer patients from a nutritional point of view. Studies show that supplementation with β-glucans promotes benefits to cancer patients undergoing chemotherapy and radiotherapy. Amino acids and β-glucans obtained from fermentation processes proved to be important in the care of cancer patients, because they improve the nutritional parameters and general condition of the patient. Thus, this work aims to discuss the benefits obtained by cancer patients undergoing chemotherapy and radiotherapy who received supplementation with a fermented nutraceutical rich in β-glucans and amino acids. A literature review was carried out through an active search for scientific articles through the use of the following descriptors in Portuguese: β-glucans, amino acids, cancer patients, chemotherapy and radiotherapy. In addition, we also discuss the benefits caused by the use of the product called Bionutri AR1®, a nutraceutical that contributes to the recovery of nutritional status, indicated for patients with severe malnutrition induced by cancer and the therapeutic approaches chemotherapy and radiotherapy. We conclude that the use of products capable of promoting supplementation of β-glucans and amino acids is extremely beneficial to cancer patients, especially those undergoing chemotherapy and radiotherapy and, therefore, there is an indication of supplementation for these patients with the fermented product Bionutri AR1®.